Radiological Knosp, Revised-Knosp, and Hardy–Wilson Classifications for the Prediction of Surgical Outcomes in the Endoscopic Endonasal Surgery of Pituitary Adenomas: Study of 228 Cases - Araujo-Castro, Marta; Acitores Cancela, Alberto; Vior, Carlos; Pascual-Corrales, Eider; Rodríguez Berrocal, Víctor (Frontiers in Oncology, 2022)
Purpose: To evaluate which radiological classification, Knosp, revised-Knosp or Hardy-Wilson classification, is better for the prediction of surgical outcomes in the endoscopic endonasal transsphenoidal (EET) surgery of pituitary adenomas (PAs). Methods: A retrospective study of patients with PAs who underwent EET PA resection for the first time between January 2009 and December 2020. Radiological cavernous sinus invasiveness was defined as a Knosp or revised-Knosp grade >2 or a grade E in the Hardy-Wilson classification. Results: 228 patients with PAs were included. Cavernous sinus invasion was evident in 35.1% and suprasellar extension in 74.6%. Overall, surgical cure was achieved in 64.3% of patients. Surgical cure was lower in invasive PAs than in non-invasive (28.8% vs 83.1%, P<0.0001), and the risk of major complications was higher (13.8% vs 3.4%, P=0.003). The rate of surgical cure decreased as the grade Knosp increased (P<0.001), whereas the risk of complications increased (P<0.001). Patients with Knosp 3B PAs achieved surgical cure less commonly than 3A PAs (22.2% vs 60.9%, P=0.049). Similar results were observed based on the invasion and extension of Hardy-Wilson classification (stage A-C 83.1% vs E 28.8% P<0.0001, grade 0-II 81.1% vs III-IV 59.7% P=0.008). The Knosp classification offered the greatest diagnostic accuracy for the prediction of surgical cure (AUC 0.820), whereas the invasion Hardy-Wilson classification lacked utility for this purpose (AUC 0.654). Conclusion: The Knosp classifications offer a good orientation for the estimation of surgical cure and the risk of complications in patients with PAs submitted to EET surgery. However, the invasion Hardy-Wilson scale lacks utility for this purpose.